Development of Online Teaching Materials for Accounting Subjects in the Covid 19 Era - Ichsan Siregar, Muhammad; Cakranegara, Pandu Adi; Anwar, Muhammad Abduh; Kamar, Karnawi; Yakub, Rahman (Edumaspul: Jurnal Pendidikan, 2022)
This research is a development research (R&D) with the aim of knowing the level of need and the level of feasibility and practicality of online teaching materials on accounting subjects with the subject of recording expenses and income. The population of this research is class X majoring in Institutional Financial Accounting as many as 120 students with a sample of 40 students of SMK Negeri 2 Sidenreng Rappang with non-probability sampling technique by purposive sampling. Online teaching materials were developed with the validation process of media and material experts, then teacher and student responses with questionnaire instruments, and limited trials. The expert validity instrument was used to measure the validity test, while the questionnaire was used to test the practicality of product assessment using a Likert scale. The data obtained from the validators and respondents were then analyzed using a descriptive percentage technique. The results of the assessment by the validator with an average value of 94.25% illustrates that the online teaching materials developed are declared very feasible. The percentage of practicality by the subject teacher is 96% and the response from students is 96.25%. Based on these results, a conclusion was drawn that online teaching materials on accounting subjects with the subject of recording expenses and income used by class X students of SMK Negeri 2 Pancarijang with the 4D development model met the criteria, namely very feasible and very practical to use in the process of teaching and learning activities systematically on line.